Implementation E-Government in supporting of online-based Service Quality and Accessibility - Avianto, Bhakti Nur; Ismowati, Marry; Amelia, Nanda (Journal Research of Social Science, Economics, and Management, 2022)
In the development of Revolution 4.0, the application of information technology is a must for state administrators (government). And also, the use of information technology in governance (e-government) is also one way to realize bureaucratic reform in improving the quality of public services to make them more effective, efficient, and transparent and accountable. The research method used is qualitative with a descriptive verification approach and in-depth interviews with various informants relevant to the study. The results of the research show that the government needs to adapt quickly to support people’s needs in a more effective and efficient way. Namely by implementing an E-government system or government that utilizes technology for a transparent, effective, efficient and accountable service to the public. This digital gap can be seen from one of the factors, namely whether or not internet access is evenly distributed and the extent of local people’s knowledge regarding digital use. Between these gaps, sometimes we feel irritated when a digital-based service is arguably of good quality in a government agency, but the gap comes from the humans themselves who have not been able to properly utilize their digital infrastructure. Therefore, the government needs more attention to monitor the ability of human resources or ASN to be more consistent with e-government based services. If the HR capabilities are still not able to utilize the e-government system properly, then the funds spent will be in vain. Apart from digital infrastructure funding, there are things that are more urgent than that, namely repairing damaged roads in the regions which of course provide direct satisfaction to the community rather than pouring digital infrastructure funds into the readiness of human resources itself which is low or cannot yet implement e governance over e government.